HYDROELECTRICITY CONSUMPTION AND ECONOMIC GROWTH NEXUS: TIME SERIES EXPERIENCE OF THREE AFRICAN COUNTRIES - Emmanuel Ziramba (European Scientific Journal, ESJ, 2013)
This paper examines the relationship between hydroelectricity and economic growth for three African countries within a multivariate framework over the period 1980-2009. Our results provide support for the neutrality hypothesis for Egypt. The feedback hypothesis is confirmed in Algeria while the conservation hypothesis is supported in South Africa. These findings imply that the authorities in Egypt and South Africa can implement conservation policies which seek to reduce hydroelectricity consumption without adversely affecting their economies‟ growth rates. The same cannot be said for Algeria where there is evidence of bi-directional causality between the two variables.